THE EVALUATION AND SELECTION OF SUPPLIERS – IN A LEAN APPROACH - Berenyi, Laszlo; Banhegyesi, Lajos (European Scientific Journal, ESJ, 2015)
Lean management has become a popular concept in the last decades, the principles permeate the present business strategies as well. Of course, lean management goes beyond the limits of one company. The real benefits are reflected if it is applied for complex supply chains. An important challenge is enhancing the lean approach to direct partners. The paper draws up the possibilities from the viewpoint of quality management that can cover the fact that a supplier is the source of both opportunities and risks. The focus is on the supplier evaluation and selection in order to explore and to prevent the potential losses of poor external compliance. Next to the theoretical reasoning the paper includes some short case studies based on the author’s experiences in order to present the limitations and the considerable good practices.